Foreign experience of implementing music therapy: training, education and professional aspects. - Dobrovolska, Rufina (Social work and education, 2023)
Answer the question "what is music therapy?" being concise and comprehensive can be difficult, especially for new students entering their studies. Most experienced practitioners can only provide a few short sentences and answers to summarize and describe their work. But when portraying their own experience and impressions of professional activity in music therapy, experienced practitioners face the problem that it is quite difficult to explain to others the relevance of the profession of music therapist. Reflecting this, many practitioners learn how to explain music therapy to others by describing their own experiences and individual cases in their own practice where the use of music has made a difference, and learn how to support and help the person. Music therapy is constantly growing in recognition internationally. Its evidence base is expanding and consolidating, so theoretical maturity is beginning to emerge. This is a good opportunity to learn and master the profession of music therapist. Choosing a career as a music therapist can be challenging and exciting. Working with music every day, facilitating positive change in people’s lives and having regular opportunities to share and collaborate with other practitioners, through teamwork and participation in national and international conferences are some of the aspects that make music therapy a fantastic job. The article discusses the definition of music therapy, as well as several components that define music therapy internationally: content and relationship to music therapy throughout the life span, models and approaches to music therapy, methods of music therapy, music therapy research, music education and professional issues.